2017
DOI: 10.1111/imm.12853
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Cryptococcus neoformans elicits allergic airway inflammation independent of Nuclear Factor Kappa B signalling in lung epithelial cells

Abstract: Pulmonary challenge with the ubiquitous fungus Cryptococcus neoformans results in allergic airway inflammation (AAI) characterized by robust recruitment of eosinophils and T cells producing type 2 cytokines to the lungs. Previous studies have demonstrated a critical role for Nuclear Factor Kappa B (NF-κB) activation within lung epithelial cells (LECs) in driving AAI in response to protein allergens, yet the role of LEC-intrinsic NF-κB in promoting AAI following exposure to C. neoformans is poorly understood. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…A protocol of surface staining for flow cytometric analysis was carried out as described previously [43,44,46,47] with minor modifications. Single cell suspensions were first stained with 1:250 fixable Live/Dead (near IR), then incubated with unlabeled FcRIII/II to block Fc receptors and subsequently stained with 1:200 dilutions of fluorescently labeled antibodies (CD45, SiglecF, CD11b, CD11c, Ly6G, Ly6C, MHCII) for 30 minutes at 4°C, resuspended in 2% paraformaldehyde and stored at 4°C protected from light until acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…A protocol of surface staining for flow cytometric analysis was carried out as described previously [43,44,46,47] with minor modifications. Single cell suspensions were first stained with 1:250 fixable Live/Dead (near IR), then incubated with unlabeled FcRIII/II to block Fc receptors and subsequently stained with 1:200 dilutions of fluorescently labeled antibodies (CD45, SiglecF, CD11b, CD11c, Ly6G, Ly6C, MHCII) for 30 minutes at 4°C, resuspended in 2% paraformaldehyde and stored at 4°C protected from light until acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…Monocyte‐derived macrophages and dendritic cells are often recruited into the airway . Likewise, other myeloid cell populations, including neutrophils, monocytes and eosinophils, infiltrate the airways in an effort to combat the infection. In almost all cases of pulmonary fungal infection, the development of adaptive immunity and the engagement of CD4 T‐cell help is a key determinant of the outcome on infection.…”
Section: Fungal Recognition and T‐cell Priming The Lungmentioning
confidence: 99%
“…[24,25,29,30]. Pulmonary eosinophilia caused by cryptococcal infection has been associated with inefficiency in controlling or resolving the pulmonary infection, culminating in a Th2 allergic response [29][30][31]. Although C. gattii-infected WT mice had chronic cryptococcal pneumonia and pulmonary eosinophilia 21 days after inoculum, we found hypereosinophilia in TLR9 -/pulmonary mixed infiltrate.…”
Section: Discussionmentioning
confidence: 63%
“…Many works have demonstrated that cryptococcal pneumonia leads to an intense and prolonged pulmonary Th2 inflammatory response. The "allergy" response is like other chronicle inflammatory diseases, such as asthma and allergic bronchopulmonary mycosis (ABPM) [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%